MEMAHAMI DOKUMENTASI - Blasius Sudarsono (Universitas Pendidikan Ganesha, 2017)
In Indonesia, documentation does not develop as a science as the library. Even the documentation is forgotten or deliberately forgotten. In the United States documentation has also been considered the past since the introduction of information science. Yet it is precisely from America too, the documentation evolved into a new science. Currently there is Document Academy Meeting (DOCAM) which is held annually on an international level. At European Tromso University became the lead pioneer of documentation studies. This development seems to escape from the view of the library school in Indonesia. This paper presents a personal journey in interpreting the documentation. It is hoped that this paper can inspire librarians practitioners and academics in the field of documentation study. Keywords: documentation, library, librarian